Pengaruh Topografi dan Vegetasi terhadap Kecepatan Angin di Daerah Pegunungan Sukabumi: Studi Observasi Lapangan - Risnatati; Yasiva Dortiana Lima; Muhammad Musyaddad; Winny Liliawati (Mataram University, 2026)
This study aims to analyze the influence of topography and vegetation on wind speed in mountainous areas. Conducted in April 2026 in Cinunjang Village, Cijulang Village, Jampang Tengah District, Sukabumi Regency, the research employed a descriptive method with direct field observation. Data were collected from three locations: a footpath surrounded by trees, a rice field area, and a residential area, using a digital anemometer and analyzed descriptively. The results showed that the highest wind speed was recorded in the rice field area (1.6 m/s), while the lowest was observed on the tree-covered footpath (0.8 m/s). The residential area recorded a wind speed of 1.5 m/s. These differences were influenced by topography, vegetation density, and land openness, which affect air circulation patterns. The findings enhance understanding of how environmental conditions influence wind speed distribution in mountainous regions and provide useful information for spatial planning, disaster risk mitigation, and environmentally responsive design.